Improving Employee Performance: Assessment of Leadership Style, Work Environment, and Work Motivation Aspects - Suwignyo Widagdo; Domingos Lemos Lopes; Helmi Agus Salim (LPPM Institut Teknologi dan Sains Mandala, 2023)
This study aims to examine the influence of leadership style, work environment and work motivation on employee performance at the Ijen sub-district office, Bondowoso district. The research data were obtained from distributing questionnaires to research objects with a sampling technique using saturated sampling. This type of research is quantitative. The respondents in this study were all employees at the Ijen sub-district office, Bondowoso district, totaling 30 people with details of 25 people with civil servant status and 5 people with contract worker status. Data analysis in this study used Validity Test, Reliability Test, t-test, F Statistic Test, Determination Coefficient. The results of this study indicate that leadership style, work environment and work motivation have a significant effect partially or simultaneously on employee performance, this is evidenced by the t count value> t table and the F count test value> F table. The coefficient of determination of 0.831 indicates that 83.1% of employee performance variations can be explained by the three variables